Experimental and numerical studies of concrete-filled high-chromium stainless steel tube (CFHSST) stub columns. (November 2019) - He, An; Wang, Fangying; Zhao, Ou
Abstract: The present paper reports a thorough experimental and numerical investigation into the compressive behaviour and load-carrying capacities of concrete-filled steel tube (CFST) stub columns with the outer tubes made of a newly developed high-chromium grade EN 1.4420 stainless steel. In comparison with the most commonly used stainless steel grades EN 1.4301 and EN 1.4404, the new grade EN 1.4420 possesses lower material price, but better corrosion resistance and higher strength, and thus has a greater potential for widespread use in composite construction. In this study, an experimental programme was firstly carried out on 15 CFST stub columns with high-chromium stainless steel tubes of five different cross-section sizes and concrete infill of three grades, as well as 5 (reference) bare high-chromium stainless steel tube stub columns. The test setup, procedure and results, including the ultimate loads, load−deformation histories and failure modes, were fully reported. The experimental investigation was supplemented by a numerical modelling study, where the developed finite element models were firstly validated against the experimentally obtained results and then utilised to perform parametric studies for the purpose of expanding the limited test data pool over a wider range of cross-section sizes. The test and numerical results were utilised to evaluate the applicability of the codified provisions, established in North America, Europe and Australia, to the design of the new concrete-filled high-chromium stainless steel tube stub columns. Overall, the examined design codes were generally found to yield safe-sided but slightly conservative resistance predictions for the new high-chromium stainless steel composite stub columns. Modifications to the codified design provisions were then made, and shown to result in an improved level of design accuracy. Highlights: Stub column tests on the new concrete-filled high-chromium stainless steel tube (CFHSST) composite members were conducted. The behaviour and strengths of CFHSST stub columns were discussed. FE models were developed to validate against test results and then conduct parametric studies. The accuracy of the current design codes to the new CFSST stub columns was assessed, indicating slightly conservative design. Modifications to the codified design provisions were made, and shown to yield more accurate and consistent design.